Effect of menopause on salivary glands and oral mucosa - Srebrzyńska-Witek, Agnieszka; Koszowski, Rafał (Menopause Review/Przegląd Menopauzalny, 2013)
Preserving natural and healthy dentition till the end of life is strongly connected with regular control visits at the dentist’s surgery and following therapeutic procedures that may be found necessary. Today’s society develops an awareness of the necessity to preserve good health of the oral cavity. Therefore, dentists attempt to provide medical care to the patients of all ages, including menopausal women. Women at the perimenopausal or post-menopausal age often experience a decrease in estrogenic hormone concentration due to discontinued endocrinological activity of the ovaries. This leads to a number of systemic implications, including the negative effect on salivary glands and oral mucosa. It is important to keep in mind that such patients may suffer from oral diseases specific to their age. This paper presents most common oral diseases that occur in women at the menopausal or perimenopausal age. While the systemic aspects of menopause are well documented, the awareness of oral discomfort as a part of menopausal complaints is still low. The authors present the current state of knowledge on how deficiency or supplementation of estrogens can affect salivary glands and oral mucosa in perimenopausal and post-menopausal women. Particular attention is paid to symptoms resulting from abnormal lubrication of oral mucosa or burning mouth syndrome, the latter quite common among menopausal women. Also, the authors describe some therapeutic methods that may be used to treat the diseases.